Knowledge and Awareness of Primary Teeth and Their Importance among Parents - A. Sai Sanjith, K. R. Don2 , Karthik Ganesh Mohanraj3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The primary dentition for children is, perhaps, the most essential and yet the most neglected concern by aparent. Often, these parents who are responsible for the health of the primary dentition of their children feelthat primary teeth eventually shed, and hence do not deserve heed to providing adequate oral health. The aimof this study was to evaluate the parental knowledge, attitude, and practices on the importance of primarydentition of their children. A well structured, self-prepared questionnaire was circulated among parents ofthe dental students within the university. The results obtained were collected and analysed to find out theawareness levels among the parents and to find out which group had the highest knowledge on primary teeth.The statistical tests used were descriptive analysis and Chi square tests. The confidence level was 95% andthe data was considered statistically significant if P value < 0.05. In our study, it was found that among theparents, graduated individuals had the highest knowledge on primary dentition, especially the Post graduatelevel parents